KONSEP PAJAK DALAM KAJIAN AL-QUR’AN DAN SUNNAH - Hakim, Ridwan (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Tax is a practice that has long been applied in world history, even in the practice of the Khilafah Islamiyah government, the concept of tax already exists. In the Qur'an there is a verse about “jizya” for disbelievers which is applied as compensation for the rights to become citizens. Likewise the verse about Dzulkarnain which alludes to “Al-Kharaj” which is more specific about taxes in general. This study uses the literature review method to examine how the Mufassir provide general provisions in the administration of taxes by the authorities. The result is that it is permissible as long as it must be based on benefit and justice, because the original rule is that human property is forbidden to be taken without a justified reason. So only the legitimate rulers can set tax rules for the general benefit. If it is taken or distributed in a vanity, the practice of taking other people's property is in  “maks” category which is strictly prohibited in the hadith.